2021
DOI: 10.1002/adem.202001185
|View full text |Cite
|
Sign up to set email alerts
|

Extra Strengthening and Work Hardening in Novel Precipitation‐Hardened FeCrNiSix Medium‐Entropy Alloys

Abstract: Precipitation strengthening is believed as an important strengthening method that optimizes the strength of alloys. Herein, the possibility of precipitation strengthening is demonstrated by introducing the intermetallic (Cr, Si)‐rich σ phase in the novel FeCrNiSix MEAs system. It is found that simultaneous enhancement in strength and work hardening can be attained by adding Si element in the FeCrNi MEA. Specifically, the FeCrNiSi0.2 alloy realizes a good balance of strength and ductility due to the precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, for VBSi–EHEA, V and B elements were enriched and the Si element was depleted in M 3 B 2 ‐type boride, which was slightly different from our initial design idea. A previous study by Chang [ 43 ] and Bai [ 51 ] also indicated that Si had a large solid solubility in FCC‐disordered solid solution. By adding 0.3Si, CoCrNi and CoFeNi HEAs still maintained a single‐phase FCC‐disordered solid‐solution structure in the as cast.…”
Section: Resultsmentioning
confidence: 93%
“…However, for VBSi–EHEA, V and B elements were enriched and the Si element was depleted in M 3 B 2 ‐type boride, which was slightly different from our initial design idea. A previous study by Chang [ 43 ] and Bai [ 51 ] also indicated that Si had a large solid solubility in FCC‐disordered solid solution. By adding 0.3Si, CoCrNi and CoFeNi HEAs still maintained a single‐phase FCC‐disordered solid‐solution structure in the as cast.…”
Section: Resultsmentioning
confidence: 93%